Chaotic differential bee colony optimization algorithm for dynamic economic dispatch problem with valve-point effects - Lu, Peng; Zhou, Jianzhong; Zhang, Huifeng; Zhang, Rui; Wang, Chao (International journal of electrical power & energy systems, 2014)
•Logistic map is applied to generate candidate solutions.•New searching mechanism and feasibility method is used to search solutions.•Chaotic local search method is used to enhance the local exploitation ability.•Applying heuristic constraint handling strategy to handle various constraints.•The effectiveness of the proposed algorithm is proved by four cases. Dynamic economic dispatch (DED) plays an important role in thermal system operation, and it also presents non-smooth and non-convex characteristics while considering valve-point effects. In this paper, chaotic differential bee colony optimization algorithm (CDBCO) is adopted to solve DED problem considering valve-point effects. To increase the global search ability, chaotic sequences are applied to generate candidate solutions and a new searching mechanism based on DE/best/1 strategy and feasibility method is used to generate new solutions. Moreover, a chaotic local search (CLS) method is used to help bee colony optimization (BCO) overcome the drawback of premature convergence and increase the local exploitation capability. During the optimal process, a heuristic constraint handling strategy is introduced to deal with the various constraints of DED problem. Finally, the feasibility and effectiveness of the proposed CDBCO algorithm is proved by four test cases units and compared with other methods reported in recent literatures. The simulation results show that the proposed method can get higher-quality solutions with short computational time.